FRI0113 Persistence and Adherence with Triple Therapy and Tumor Necrosis Factor Inhibitor-Methotrexate Combination Therapy in us Veterans with Rheumatoid Arthritis. (9th June 2015) - Cannon, G.W.; Teng, C.C.; Tang, D.H.; Leng, J.; Harrison, D.J.; Sauer, B.
Abstract : Background: A randomized controlled trial (RTC) including US veterans with rheumatoid arthritis (RA) reported similar clinical efficacy, persistence, and adherence in a comparison of combination therapy with triple therapy (methotrexate [MTX] + hydroxychloroquine [HCQ] + sulfasalazine [SSZ]) versus tumor necrosis factor inhibitor-methotrexate (TNFi-MTX). 1 In contrast, an analysis of US clinical practice based on claims data for commercially insured patients reported differences in persistence and adherence between these combinations. 2 Objectives: To report one-year persistence and adherence of triple therapy and TNFi-MTX in US Veterans initiating combination therapy to allow preliminary comparison of findings in clinical practice and RCT-reported data. Methods: US veterans with RA initiating TNFi-MTX or triple therapy between Jan 1, 2006 and Dec 31, 2012 after 6-months of VA enrollment without prior combination therapy were evaluated for 12-months. The index date for starting combination therapy was defined as the date on which the final drug to complete each treatment combination was initiated. Three different definitions for termination of combination therapy were defined and persistence over one year calculated for each method. Method #1: ≥45-day gap for the TNFi or two drugs in triple therapy, or initiation of a non-TNFi biologic or new conventional DMARD; method #2: Same as #1 except switch to another TNFi in TNFi+MTX group or change in conventional DMARD was allowed; method #3: ≥45-day gap in any drug of the combination or initiation of any new biologic or conventional DMARD. Persistence on individual drugs within each therapy was assessed and defined as no ≥45-day gap for that drug. Adherence was defined as Proportion of Days Covered (PDC)>80% and determined for each individual drug and the combination of all drugs. Results: A total of 2, 936 TNFi-MTX patients and 1, 125 triple therapy patients met the eligibility criteria (mean [SD] age at index 60.7 [10.8] vs. 61.8 [9.9], 13.0% vs. 9.0% female, mean [SD] Charlson comorbidity index 1.61 [1.03] vs. 1.81 [1.36]). After 12 months, persistence in the TNFi-MTX arm was significantly greater across all three approaches (p<0.0001). Adherence to the combination protocol for all drugs was higher for TNFi-MTX patients than triple therapy patients over the course of the first year (25.1% vs. 17.2%, p<0.0001). Persistence and adherence to individual drugs in the combination therapies substantially varied (range of persistence rates [26.6%, 49.8%]; range of adherence rates [29.4%, 49.3%]), with the lowest persistence and adherence occurring in SSZ users (persistence rate 26.6%; adherence rate 29.4%). Conclusions: US Veterans initiating TNFi-MTX therapy consistently showed significantly greater persistence and adherence than those initiating triple therapy during clinical practice in contrast to similar persistence and adherence reported with these combinations in a clinical trial. References: O'Dell et al. N Engl J Med 2013;369:307-318. Bonafede et al. Ann Rheum Dis 2014;73:Suppl 2;335. Acknowledgements: Research funded by Immunex Corporation, a wholly owned subsidiary of Amgen Inc. Disclosure of Interest: G. Cannon Grant/research support from: Amgen, C. C. Teng Grant/research support from: Amgen, D. Tang Shareholder of: Amgen, Employee of: Amgen, J. Leng Grant/research support from: Amgen, D. Harrison Shareholder of: Amgen, Employee of: Amgen, B. Sauer Grant/research support from: Amgen